Comparing Mental Health of US Children of Immigrants and Non‐Immigrants in 4 Racial/Ethnic Groups. (14th January 2018) - Kim, JaHun; Nicodimos, Semret; Kushner, Siri E.; Rhew, Isaac C.; McCauley, Elizabeth; Vander Stoep, Ann
ABSTRACT: BACKGROUND: To compare the mental health status of children of immigrant (COI) and non‐immigrant (NI) parents and to determine whether differences in mental health status between COI and NI vary across 4 racial/ethnic groups. METHODS: We conducted universal mental health screening of 2374 sixth graders in an urban public school district. To screen, we administered well‐validated adolescent depression and disruptive behavior problem questionnaires. We evaluated associations between child mental health, parent immigration status, and race/ethnicity using binomial regression. RESULTS: Among Asian American/Pacific Islanders and Latinos, COI had significantly higher depression and disruptive behavior scores compared to NI. For Blacks/African Americans, children of NI parents had significantly higher disruptive behavior scores compared to COI. For European Americans, scores of COI and NI did not differ and were relatively low. CONCLUSION: Our study suggests that how the emotional health of COI is faring relative to children of NI depends on the child's race/ethnicity.